(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2007)
In this article a framework for value-driven research is proposed. The research is based on a qualitative research approach seen from a reformational perspective. This framework has essentialy four compoments: the ethical knowledge framework and paradigm, the context, the ethical analysis and judgements and the outcome and measurement of the impact of the decisions on the ethics of a research activity. Each part of the framework follows on the previous component. This framework is based upon the assumption that no research should be without an ethical framework. In addition, the need for a value-driven approach to research is demanded by four developments: the economic value of knowledge, new developments in biotechnology, intellectual property and career-professional standards. Examples are taken from theological ethics.